"If He Has it, We Know What to Do": Parent Perspectives on Familial Risk for Autism Spectrum Disorder. (25th November 2019) - MacDuffie, Katherine E; Turner-Brown, Lauren; Estes, Annette M; Wilfond, Benjamin S; Dager, Stephen R; Pandey, Juhi; Zwaigenbaum, Lonnie; Botteron, Kelly N; Pruett, John R; Piven, Joseph; Peay, Holly L; ,
Abstract: Objective: Predictive testing for familial disorders can guide healthcare and reproductive decisions. Familial disorders with onset in childhood (e.g., autism spectrum disorder [ASD]) are promising targets for presymptomatic prediction; however, little is known about parent perceptions of risk to their children in the presymptomatic period. The current study examined risk perceptions in parents of infants at high familial risk for ASD enrolled in a longitudinal study of brain and behavior development. Methods: Semistructured interviews were conducted with 37 parents of high-risk infants during the presymptomatic window (3–15 months) that precedes an ASD diagnosis. Infants were identified as high familial risk due to having an older sibling with ASD. Parent interview responses were coded and interpreted to distill emerging themes. Results: The majority of parents were aware of the increased risk of ASD for their infants, and risk perceptions were influenced by comparisons to their older child with ASD. Parents reported a variety of negative emotions in response to perceived risk, including worry, fear, and sadness, and described impacts of perceived risk on their behavior: increased vigilance to emerging symptoms, altered reproductive and healthcare decisions, and seeking ongoing assessment through research. Conclusions: Parents of children at high familial risk for childhood-onset disorders like ASD face a period of challenging uncertainty during early development. In anticipation of a future in which presymptomatic testing for ASD is made available, it is important to understand how parents react to and cope with the elevated—but still highly uncertain—risk conveyed by family history.